Pengembangan Metode Steam Sebagai Upaya Peningkatan Kemampuan Anak Usia 5-15 Tahun Di Tangerang Selatan - Aurelia Tari Fortuna; Yanda Bara Kusuma (Universitas 45 Surabaya, 2023)
Education is an important topic to investigate in depth since providing proper learning is one approach to increase the quality and competitiveness of human resources. Children will face increasingly difficult problems in the twenty-first century, beginning with increasingly strong competition and the need for increasingly complicated technologies to sustain lives that are increasingly intertwined with technology. Children between the ages of 5 and 15 have a high level of curiosity, and their exploratory abilities develop quickly because they are fostered by school activities. The STEAM method is a multidisciplinary learning approach that incorporates Science, Technology, Engineering, Art, and Mathematics. This strategy can help children solve difficulties and develop their imagination.